Does brand orientation lead to brand loyalty among senior and top management in a South African business-to-business organisation? - Gail M. Dludla; Siphiwe Dlamini (South African Journal of Business Management, 2018)
Background: At the heart and depth of building a strong and prosperous brand in the marketplace, is brand orientation. A few studies have investigated the conceptualisation of brand orientation in relation to brand loyalty, as well as the involvement of brand commitment and brand trust in mediating this association in the business-to-business (B2B) environment.Objective: It is the objective of this study to examine the impact of brand orientation on brand loyalty and the roles played by brand commitment and brand trust in mediating the impact in the South African B2B environment.Method: Questionnaires were completed by 261 top and senior managers of a B2B organisation in South Africa. Structural equation modelling and smart partial least squares were employed in this study to examine the relationships between the constructs.Results: This study provides empirical evidence that brand orientation has a positive and significant relationship with brand commitment and and brand trust. Also that brand commitment and brand trust have positive and significant relationships with brand loyalty in the South African B2B context.Conclusion: This means that organisations that operate in the B2B environment should focus on brand orientation and develop brand strategies that recognise the importance of brand trust and brand commitment.
Keywords: 650